2020
DOI: 10.2196/17251
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Message Frame-Tailoring in a Web-Based Smoking Cessation Program: Randomized Controlled Trial

Abstract: Background The content of online computer-tailored interventions is often determined to match an individual’s characteristics, beliefs, and behavioral factors. These content-tailored interventions lead to better message processing and a higher likelihood of behavior change such as smoking cessation. However, a meta-analysis of online computer-tailored interventions showed that effect sizes, albeit positive, remain small, suggesting room for improvement. A promising strategy to enhance the effective… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 39 publications
1
17
0
2
Order By: Relevance
“…Greater perceived message relevance was associated with higher perceived susceptibility, which in turn predicted CRC screening intentions. These findings support previous literature on the benefits of tailored risk messages [ 5 , 6 , 11 , 40 , 41 ] and provide further insight into the theoretical mechanisms that underlie the efficacy of this approach.…”
Section: Discussionsupporting
confidence: 88%
“…Greater perceived message relevance was associated with higher perceived susceptibility, which in turn predicted CRC screening intentions. These findings support previous literature on the benefits of tailored risk messages [ 5 , 6 , 11 , 40 , 41 ] and provide further insight into the theoretical mechanisms that underlie the efficacy of this approach.…”
Section: Discussionsupporting
confidence: 88%
“…Past studies have demonstrated baseline cognitive perceptions about quitting as a predictor of enrollment in cessation trials [ 44 , 53 ]. Consistent with the elaboration likelihood model, greater perceptions of message relevance are associated with high-involvement processing and greater motivations to adhere to recommendations made within a message [ 20 , 54 , 55 ]. Perceived message relevance has been demonstrated to be important at predicting intentions within other smoking behavior contexts, but is a novel finding in predicting research participation.…”
Section: Discussionmentioning
confidence: 83%
“…At the time of the search update, the full text of Kahler [ 34 ] was not available, and thus, the details required for the meta-analysis could not be extracted. Additionally, due to unclear details regarding the control intervention, we excluded the study by Altendorf et al [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…When the 6 studies [ 23 - 25 , 28 , 30 , 35 ] that reported attrition at 3-month follow-up were pooled ( Figure 4 ), no significant differences were found in the risk of attrition between the tailored interventions and their untailored controls (RR=0.99, 95% CI 0.95-1.04; P =.80) with high heterogeneity in the estimate ( I 2 =73%). This finding suggests that tailoring had no effect on dropout attrition at 3-month follow-up.…”
Section: Resultsmentioning
confidence: 99%